2018
DOI: 10.1108/jmtm-02-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Managing reversed (global) outsourcing – the role of knowledge, technology and time

Abstract: Purpose Against the recent trend toward reversed global outsourcing, the purpose of this paper is to provide insights on how the internal process can be handled once the decision on reverse outsourcing has been made. The authors focus in particular on in-house knowledge and technology requirements. Design/methodology/approach To explore the topic at hand, the researchers conducted in-depth semi-structured interviews with five companies operating in two different industry sectors. Findings Reversed outsourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 62 publications
0
59
0
Order By: Relevance
“…In fact, over time, the previous knowledge base in the home country might be diminished, and neglecting to evaluate the access to skills and knowledge can turn out to be a fatal error for reshoring implementation (Nujen and Halse 2017). In such a context, the management role in identifying existing competences and developing dynamic capabilities becomes fundamental (Nujen et al 2018a). Surprisingly, also articles with a focus far away from the preparation phase mention details that help in structuring its characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, over time, the previous knowledge base in the home country might be diminished, and neglecting to evaluate the access to skills and knowledge can turn out to be a fatal error for reshoring implementation (Nujen and Halse 2017). In such a context, the management role in identifying existing competences and developing dynamic capabilities becomes fundamental (Nujen et al 2018a). Surprisingly, also articles with a focus far away from the preparation phase mention details that help in structuring its characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Fredriksson and Johansson, 2009). Nujen et al (2018) have also shown that backshoring strategies are affected by how the capability gap have been dealt with during the outsourcing/offshoring period. Thus, going back to the discussion of the increasing transfers to subsidiaries and the backshoring trend, also for outsourcing/offshoring companies, there is a need to develop strategies for keeping an alignment between the motives of the decision and how to organise the realization.…”
Section: Strategies Of Business Agreementmentioning
confidence: 99%
“…the why (e.g. Fratocchi et al 2014;Stentoft et al, 2016;Fratocchi et al 2017;Nujen et al, 2018). However, the question of how to carry out the decision, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the literature grows on reversal of offshoring decisions (e.g. Gylling, Heikkilä, Jussila, & Saarinen, 2015;Stentoft et al, 2016;Nujen et al, 2018), and as more attention is devoted to the bi-directionality of global movements of manufacturing activities (Vanchan, Mulhall, & Bryson, 2018) most research still focus on production either at home or far offshore. Research on moving or relocating production to the near-abroad has not received the same attention, even though empirical studies show evidence of trends towards 'regional rebalancing of value chains' (Backer et al, 2016) and high company interest in opportunities provided by nearshoring (Miebach Consulting, 2017).…”
Section: Nearshoring Of Production: Notes From the Literaturementioning
confidence: 99%